“Fomsumerism” and beauty consumerism among social media users in Malaysia / Ahlam Abdul Aziz, Nurfarhanah Hasnuden and Wardatul Hayat Adnan - Abdul Aziz, Ahlam; Hasnuden, Nurfarhanah; Adnan, Wardatul Hayat (Universiti Teknologi MARA, 2021)
‘Fomsumerism’ comes from a present-day social expression used in allusion to someone who have the emotional experience of generally attached with social media that is FOMO (Fear of Missing Out). This study explains the concept of ‘Fomsumerism’ and its connections with consumer behaviour which lead to consumerism. ‘Fomsumerism’ that trigged from social media conductive to consume beauty products as what they view from their wall. This will apply to those who are concern about the beauty products and will ensure that they will be the pioneer of having the product.